Fibrosis progression in chronic hepatitis C virus infection - McCaughan, G W (Copyright 2004 by Gut, 2004)
Chronic hepatitis C virus infection is typically characterised by slowly progressive hepatic fibrosis. However, it is recognised that some patients do not progress while others rapidly develop significant fibrosis. Here, we review studies that have assessed factors that could influence this rate of fibrotic progression.